2007
DOI: 10.1111/j.1740-0929.2007.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as an indicator for carcass composition in farm animals

Abstract: The function of leptin in livestock species has been intensively studied during recent years. Due to the associations between plasma leptin concentrations and body fat, leptin could be used as an indicator for the in vivo evaluation of carcass composition in breeding programs. This review specifically discusses leptin mRNA expression in several fat tissues, the relationship between plasma leptin and body fat and the influence of fasting on this association. It also refers to the limitations of the use of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…They concluded that early leptin concentrations were not at all or only slightly associated with BF, plasma leptin concentrations immediately before slaughter correlated more strongly with this fat characteristic. Altmann and von Borell (2007) inferred from a review of numerous studies that estimation of body fat at slaughter based on leptin concentration in early life provides little information. For that reason, the potential for use of plasma leptin as a selection tool in breeding programs is limited because the leptin concentration is related to the fat accumulation at the point of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that early leptin concentrations were not at all or only slightly associated with BF, plasma leptin concentrations immediately before slaughter correlated more strongly with this fat characteristic. Altmann and von Borell (2007) inferred from a review of numerous studies that estimation of body fat at slaughter based on leptin concentration in early life provides little information. For that reason, the potential for use of plasma leptin as a selection tool in breeding programs is limited because the leptin concentration is related to the fat accumulation at the point of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and Gibson (1999) reported a lack of association between polymorphisms of the leptin gene and adiposity within 4 breeds of pigs exhibiting high and low BF. The associations between carcass characteristics and specific leptin gene polymorphisms are often population-specific and vary across studies, although the polymorphisms have been demonstrated to be functional (Altmann and von Borell, 2007). Further study is necessary to clarify these associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kumar et al (1998) reported that the expression of leptin mRNA in omental, perirenal and subcutaneous fat tissue was similar in lambs. The level of leptin gene expression may reflect considerable differences among adipose tissues and the reason is not known yet why the leptin expressions are various in different fat depots (Altmann and von Borell 2007). In the light of these findings it can be concluded that leptin is not a strong predictor but it offers an opinion and on the other hand, BW and UFT were not the predictors for omental fat in male Awassi lambs.…”
Section: Estimation Of Fat Tissues and Fat Amount From Leptinmentioning
confidence: 44%
“…Therefore, fat tail cannot be considered as a simple body fat and it cannot be reflected in serum leptin level. Additionally, regional variations in fat deposition can affect serum leptin level (Altmann and von Borell 2007). In other words, every fat tissue cannot affect the serum leptin level.…”
Section: Relationship Between Leptin and Fat Tissues Amountmentioning
confidence: 99%